Spatial models can improve the experimental design of field‐based transplant gardens by preventing bias due to neighborhood crowding. Issue 12 (14th December 2022) - Zaiats, Andrii; Requena‐Mullor, Juan M.; Germino, Matthew J.; Forbey, Jennifer S.; Richardson, Bryce A.; Caughlin, T. Trevor
Abstract: Field‐based transplant gardens, including common and reciprocal garden experiments, are a powerful tool for studying genetic variation and gene‐by‐environment interactions. These experiments assume that individuals within the garden represent independent replicates growing in a homogenous environment. Plant neighborhood interactions are pervasive across plant populations and could violate assumptions of transplant garden experiments. We demonstrate how spatially explicit models for plant–plant interactions can provide novel insights on genotypes' performance in field‐transplant garden designs. We used individual‐based models, based on data from a sagebrush ( Artemisia spp.) common garden, to simulate the impact of spatial plant–plant interactions on between‐group differences in plant growth. We found that planting densities within the range of those used in many common gardens can bias experimental outcomes. Our results demonstrate that higher planting densities can lead to inflated group differences and may confound genotypes' competitive ability and genetically underpinned variation. Synthesis. We propose that spatially explicit models can help avoid biased results by informing the design and analysis of field‐based transplant garden experiments. Alternately, including neighborhood effects in post hoc analyses of transplant garden experiments is likely to provide novel insights into the roles of biotic factors and density dependence in genetic differentiation. Abstract : Neighborhood interactions in common gardens: spatial models provide novel insights into spatial interactions among neighboring plants that can alter experimental outcomes. While the paper presents two approaches to the treatment of spatial interactions, it also outlines opportunities for incorporating genotype‐mediated biotic interactions into designs and analyses of common garden studies. Resumen: Los experimentos de trasplante de especies en parcelas de campo experimentales, tanto bajo condiciones ambientales comunes ("common gardens") como diferentes ("reciprocal gardens"), son una poderosa herramienta que permite estudiar la variación genética y la interacción entre el genoma y el medio ambiente. Dichos experimentos asumen que los individuos dentro de una misma parcela representan réplicas independientes creciendo bajo condiciones ambientales homogéneas. Las interacciones entre plantas vecinas están omnipresentes en las dinámicas poblaciones y pueden suponer una violación de dichas asunciones. Sin embargo, enfoques cuantitativos que permitan evaluar la adecuación del diseño experimental son escasos. Nosotros demostramos cómo los modelos espacialmente explícitos para las interacciones planta‐planta pueden proporcionar nuevos hallazgos sobre el rendimiento genotípico en el diseño de experimentos de trasplante. Utilizamos modelos basados en individuos, junto con datos de "artemisa" ( Artemisia spp. ) procedentes de un "common garden, " para simular el impacto de las interacciones planta‐planta sobre las diferencias de crecimiento entre grupos. Encontramos que la densidad de siembra utilizada con frecuencia en muchos "common gardens" puede sesgar la estimación de la variación entre grupos. Nuestros resultados demuestran que una mayor densidad de siembra puede inflar las diferencias entre grupos, confundir la habilidad competitiva de los genomas y la variabilidad sustentada genéticamente, introduciendo así un sesgo en el experimento. Proponemos que los modelos espacialmente explícitos pueden ayudar a evitar el sesgo en los resultados mediante el apoyo en el diseño y análisis de experimentos de trasplante. Incluir efectos de vecindad en el análisis a posteriori de experimentos puede proporcionar nuevos hallazgos sobre el papel de los factores bióticos y densidad‐dependientes en la diferenciación genética.